2020
DOI: 10.3390/w12113158
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Clogging Results in Undeveloped Hardpan and Soil Mineral Leakage in the Rice Terraces in the Philippine Cordilleras

Abstract: Rice terraces in Cordillera, Philippines, a world cultural heritage site, are threatened by the risk of collapse. It is crucial to manage these rice terraces for their conservation, while simultaneously practicing traditional farming. We examined the soil environment and investigated its effects on rice terrace conservation, by focusing on the hardpan condition; infiltration process, which is related to the collapse of rice terraces; and soil nutrition conditions in these sites. Field survey and soil analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Kurozumi and colleagues [18] presented an innovative investigation about the role of hardpans in rice terraces of the Philippine Cordilleras. Based on field surveys and soil analyses, they showed that the hardpan was not sufficiently developed in areas where organic matter content was high, suggesting organic matter clogging.…”
Section: Overview Of the Special Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurozumi and colleagues [18] presented an innovative investigation about the role of hardpans in rice terraces of the Philippine Cordilleras. Based on field surveys and soil analyses, they showed that the hardpan was not sufficiently developed in areas where organic matter content was high, suggesting organic matter clogging.…”
Section: Overview Of the Special Issuesmentioning
confidence: 99%
“…Some of the papers presented in the Special Issue also highlighted the importance of advanced hydrological analyses at the terraced landscape scale [14,18,20]. Such approaches are not frontier research, but the papers submitted considered different and heterogeneous case studies (Moroccan Anti-Atlas, Ethiopian and Philippine rice terraces), which were understudied under this point of view, and which therefore could be further explored.…”
Section: Case Studiesmentioning
confidence: 99%